2022
DOI: 10.1021/acs.jctc.2c00094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Degrees of Freedom on Calculating Diffusion Properties in Nanoporous Materials

Abstract: If one carries out a molecular simulation of N particles using periodic boundary conditions, linear momentum is conserved, and hence, the number of degrees of freedom is set to 3N – 3. In most programs, this number of degrees of freedom is the default setting. However, if one carries out a molecular simulation in an external field, one needs to ensure that degrees of freedom are changed from this default setting to 3N, as in an external field the velocity of the center of mass can change. Using the correct deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…When carrying out small-scale NVT simulations, special attention should also be paid to the default settings (thermostat implementation and effective number of dof) in the specific MD code. Very recently Xu et al 14 demonstrated the importance of correct dof setting by calculating diffusion in nanoporous materials; incorrect settings are particularly disruptive when only a subset of atoms is coupled to a thermostat, or isolated non-continuous systems are simulated. In addition to the fact that the Langevin thermostat realizes correct kinetic energy distributions irrespective of the dof settings, 14 we have demonstrated that in gas-phase simulations it leads to perfect thermalization and equipartition with a minimal computational effort, making it an ideal choice for system initialization, where dynamics are secondary.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When carrying out small-scale NVT simulations, special attention should also be paid to the default settings (thermostat implementation and effective number of dof) in the specific MD code. Very recently Xu et al 14 demonstrated the importance of correct dof setting by calculating diffusion in nanoporous materials; incorrect settings are particularly disruptive when only a subset of atoms is coupled to a thermostat, or isolated non-continuous systems are simulated. In addition to the fact that the Langevin thermostat realizes correct kinetic energy distributions irrespective of the dof settings, 14 we have demonstrated that in gas-phase simulations it leads to perfect thermalization and equipartition with a minimal computational effort, making it an ideal choice for system initialization, where dynamics are secondary.…”
Section: Discussionmentioning
confidence: 99%
“…Some standard thermostats are, however, problematic as they do not produce a proper canonical ensemble and/or are prone to introduce spurious unphysical dynamics to the simulated system. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Perhaps the most famous of such thermostatting problems is the so-called "flying ice cube" effect, 1,2,15 which arises from unphysical transfer of kinetic energy from fast to slow modes of motion, causing the system's vibrational modes to freeze, while simultaneously resulting in enormous translational and rotational energies. These kinds of violations of the equipartition theorem, which states that the thermal energy should be equally distributed over the system's degrees of freedom (dof), ultimately affect the structural, dynamic, and thermodynamic properties of the simulated system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For all MD simulations, we used the LAMMPS package with the Nose-Hoover thermostat for controlling the temperature. The detailed settings follow the protocol suggested in the literature for infinite dilution 47 .…”
Section: Membrane Separationmentioning
confidence: 99%